CONTEMPORARY ISSUES ABORTION LATER DATE - Кравченко, Елена Николаевна; Коломбет, Екатерина Валерьевна; Куклина, Лариса Владимировна (Mother and Baby in Kuzbass, 2017)
Presented literature review covers issues of relevance and statistics of abortions in later stages, regulatory documents, methods of abortion in the second trimester, complications of their conduct, said the security methods of induced abortion.
Keywords: methods of abortion; later date; the second trimester